PENGARUH KARAKTERISTIK PERUSAHAAN DAN CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA - BRYAN SEBASTIAN; IRWANTO HANDOJO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2019)
The aim of this study is analysing the impact of firm size, leverage, corporate growth, cash, commissioner size, commissioner proportion, audit committee size, managerial ownership, profitability, and audit size on earnings management in non-financial companies listed in Indonesian Stock Exchange. The earningsmanagement measurement is by using the ‘Modified Jones’ model, which is the ‘discretionary accruals’ as the proxy of earnings management. The population of this study is the non-financial companies listed in Indonesian Stock Exchange during 2013 - 2016. There are 100 companies used as sample which is obtained through purposive sampling. Multiple regression is used for data analysis. The result of this research shows that leverage, cash, commissioner size, and profitability have significant influence on earnings management, while firm size, corporate growth, commissioner proportion, audit committee size, managerial ownership, and audit size have insignificant influence on earnings management.